Peran Majelis Permusyawaratan Ulama Aceh dalam Pembinaan Aliran Sesat di Aceh Barat - Muslem Hamdani (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
This study aims to explore the fatwas of Ulema's Consultative Assembly (UCA) about the heretical sect and the method of teaching they employ. The author wishes to study how the method of teaching towards the Laduni sect. Mentioned, focusing on the matter of the method of teaching that has been carried out by those from Ulema's Consultative Assembly (UCA) of West Aceh and the process that Ulema's Consultative Assembly (UCA)  of Aceh used in detecting the Laduni sect as heretical sect giving rise to an advisory opinion. For the data collection in answering this question, the author used the descriptive qualitative research method, which was the research on how the guidance is conducted by the UCA of West Aceh regency to the Laduni sect. The results showed that the origin of the Laduni sect was not known for certain, therefore it is a new sect. At this point, the new Laduni sect has twenty members. The identification was carried out through open dialogue with the followers of the Laduni sect with a persuasive approach and deep study of the understandings they developed. The patterns of guidance for the followers of the Laduni sect was conducted through the short course, which was held at the West Aceh regency police headquarters hall, through face-to-face education, consultation, and questions and answer, by presenting several speakers from both the regency and province level.